Integrated farming system for productivity and sustainability in agricultural production - JOSHI, NEESHU; JOSHI, SHOURABH; JINGER, DINESH (Indian Farming, 2022)
With 16.8% of the world’s population and less than 2.4% of world’s arable land, India is confronted with several challenges in agricultural development. Food security, employment, income generation, resource conservation and environmental protection have emerged as major world concerns. Within the sustainable agriculture framework, Integrated Farming System (IFS) is one approach towards transforming the idea of sustainable development from concept to reality. Integrated farming system can ensure the highest standard of food production with the minimum environmental impact and thereby, improving the the quality of life of farmers. More importantly, IFS helps to maintain sustainability in farm production and productivity even under highly vulnerable climatic conditions with the available resources accessible to the farmer. The goal of attaining social equity and inclusive growth can’t be achieved without providing livelihood and nutritional security to the most vulnerable sections of the indian population which consist of mostly scheduled tribes and castes. The population of tribal farmers is high inthe central tribal belt in the middle part of the country which includes southern Rajasthan, Madhya Pradesh, North eastern Gujarat, Vidarbha region of Maharashtra and Chhattisgarh.